2016
DOI: 10.1016/j.biortech.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina cultivation with a CO2 absorbent: Influence on growth parameters and macromolecule production

Abstract: The objective of this study was to select a concentration of CO2 absorbents to supplement Spirulina sp. LEB 18 cultivation and to evaluate the effect of these compounds on the growth and production of macromolecules. Three initial biomass concentrations (X0), eight concentrations of monoethanolamine (MEA), and three NaOH concentrations were tested. The selected MEA concentrations did not inhibit the growth of Spirulina and doubled the dissolved inorganic carbon concentration in the assay medium in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Some studies have shown that low concentrations (up to 300 ppm) of MEA can be used as a CO2 absorbent in the medium to enhance CO2 solubility and improve the growth of various microalgae (Scenedesmus sp., Spirulina sp.) [43,44]. However, MEA is a toxic chemical.…”
Section: Effect Of Mea and Pg Toxicity On The Growth Of Chlorella Spmentioning
confidence: 99%
“…Some studies have shown that low concentrations (up to 300 ppm) of MEA can be used as a CO2 absorbent in the medium to enhance CO2 solubility and improve the growth of various microalgae (Scenedesmus sp., Spirulina sp.) [43,44]. However, MEA is a toxic chemical.…”
Section: Effect Of Mea and Pg Toxicity On The Growth Of Chlorella Spmentioning
confidence: 99%
“…It is reported that up to 7% of global CO 2 emissions can be attributed to the anthropogenic emission of CO 2 from coal-fired thermoelectric plants (Morais and Costa, 2007). With respect to CO 2 sequestration, different technologies have been investigated, such as using amines or solid adsorbents (da Rosa et al, 2016;Sepulveda et al, 2019). Cardias et al (2018) reported that the growth of Spirulina sp.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of MEA (0.13 g MEA g biomass −1 ), an increase in protein concentration by 17% was reported (Rosa et al . ). On the contrary, the growth in biomass depends on the types of solvent and microalgae employed (Kim et al .…”
Section: Summary and Future Perspectivementioning
confidence: 97%
“…Various bacteria, algae and their CAs have been reported as having a positive effect on the process parameters of post-combustion CO 2 capture (Vinoba et al 2013;Ye and Lu 2014;Salmon and House 2015). In the presence of MEA (0.13 g MEA g biomass À1 ), an increase in protein concentration by 17% was reported (Rosa et al 2016). On the contrary, the growth in biomass depends on the types of solvent and microalgae employed Sun et al 2015).…”
mentioning
confidence: 97%